Flexible Gallium Nitride: Flexible Gallium Nitride for High‐Performance, Strainable Radio‐Frequency Devices (Adv. Mater. 47/2017). Issue 47 (14th December 2017) - Glavin, Nicholas R.; Chabak, Kelson D.; Heller, Eric R.; Moore, Elizabeth A.; Prusnick, Timothy A.; Maruyama, Benji; Walker, Dennis E.; Dorsey, Donald L.; Paduano, Qing; Snure, Michael
Abstract : In article number1701838, Nicholas R. Glavin and co‐workers describe the use of a series of flexible gallium nitride radio‐frequency devices for power amplification of wireless signals at high frequencies for future wearable and conformal electronics. The flexible GaN, in this case, is realized through epitaxial lift‐off using a 2D h‐BN release layer and can accommodate strains up to 0.43% with performance rivaling that of rigid GaN materials.